The impacts of unmet supportive care needs of cancer survivors in Australia: A qualitative systematic review. (12th October 2022) - Bellas, Olivia; Kemp, Emma; Edney, Laura; Oster, Candice; Roseleur, Jackie
Abstract: Introduction: Cancer incidence and survivorship are increasing worldwide. With more people living through and beyond cancer, there is a subsequent increase in their supportive care needs. This systematic review of qualitative studies aimed to describe the impacts of unmet supportive care needs on cancer survivors in Australia. Methods: Databases MEDLINE, EMBASE and Scopus were searched, and after screening and applying eligibility criteria, 27 qualitative studies were included. Findings were synthesised according to the Supportive Care Framework for Cancer Care, including informational, physical, practical, emotional, psychological, social and spiritual need domains. Results: The systematic review identified impacts of unmet informational, physical, practical, emotional and psychological needs. Frequently identified impacts of unmet informational needs were feelings of abandonment and isolation, distress, confusion and regret. Common impacts of unmet physical and practical needs were financial burden and return‐to‐work difficulties. Over half of all unmet supportive care needs caused emotional and psychological impacts. Conclusions: Findings identify the detrimental emotional and psychological impacts resulting from a range of unmet supportive care needs. The review highlights the interconnections between supportive care need domains thereby enhancing the understanding of the impacts of unmet SCNs. Findings may inform policy and practice change to improve supportive cancer care.